Prediction of neonatal survival according to lung‐to‐head ratio in fetuses with right congenital diaphragmatic hernia (CDH): A multicentre study from the Latin American CDH Study Group registry. (3rd December 2021) - Cruz‐Martínez, Rogelio; Molina‐Giraldo, Saulo; Etchegaray, Adolfo; Ventura, Walter; Pavón‐Gómez, Néstor; Gil‐Guevara, Enrique; Villalobos‐Gómez, Rosa; Luna‐García, Jonahtan; Gámez‐Varela, Alma; Martínez‐Rodríguez, Miguel; López‐Briones, Hugo; Chávez‐González, Eréndira; et al.
Abstract: Objective: To evaluate survival outcomes of fetuses with right sided congenital diaphragmatic hernia (CDH) treated in Latin American centres and to assess the utility of left lung area to predict neonatal survival. Methods: A retrospective cohort including isolated right sided CDH cases managed expectantly during pregnancy in six tertiary centers from five Latin American countries. The utility of the observed/expected lung‐to‐head ratio (O/E‐LHR) in predicting neonatal survival was assessed, and the best cut‐off to predict prognosis was automatically selected by decision tree analysis. Results: A total of 99 right sided CDH cases were recruited, 58 isolated fetuses were selected at a median gestational age of 26.2 weeks, showing an overall survival rate of 26.2%. A linear trend was observed between survival and the O/E‐LHR, showing that at higher O/E‐LHR, the greater probability of survival ( r  = 0.56, p  < 0.001). O/E‐LHR discriminates two groups with different survival outcomes: fetuses with an O/E‐LHR ≥65% showed a significantly higher survival rate than those with an O/E‐LHR <65% (81.8% vs. 15.6%, p  < 0.01). Conclusions: Overall survival rate in right sided CDH is lower in Latin American countries. The severity category of pulmonary hypoplasia should be classified according to lung area and the survival rate in such population. Key points: What is already known about this topic? Isolated left congenital diaphragmatic hernia (CDH) is associated with high perinatal mortality secondary to lung hypoplasia and pulmonary hypertension. The risk of neonatal death is higher in prenatally diagnosed right sided CDH than left CDH. The only parameter to classify the degree of lung hypoplasia and to predict the risk of neonatal survival in right‐sided CDH is evaluation of the observed/expected lung‐to‐head circumference ratio (O/E‐LHR). In North American and European countries, those fetuses with O/E‐LHR <45% are considered severe cases since this group shows overall survival rate of less than 17%. What does this study add? This report describes neonatal survival according to O/E‐LHR in fetuses with right congenital diaphragmatic hernia (CDH) managed expectantly during pregnancy in Latin American countries and demonstrates that overall survival rate in these countries is lower than European and North American countries, and that severe pulmonary hypoplasia in such centers should be defined by an O/E‐LHR below 65%, since this subgroup shows an overall survival rate of about 15%.